A question of addressing the real issues of the Nigerian Police operatives’ ineffectiveness for improved petormance - Okwuwa, Charles Onuora; Ololo, Kennedy O.; Owonibi, Elizabeth O. Owonibi; Emmanuel, Emelda I.; Dauda, H. Juliana. (Advances in Social Sciences Research Journal, 2020)
The Nigerian Police ineffectiveness in internal security services is a national challenge. The police have been labelled unfriendly and discredited by many due to their personal experiences and media reports. Research findings indicate that with the police, Nigerians are among the worst Police victims of human rights violations in Africa, due to corruption, unlawful and prolonged detention without trials and various unprofessional conduct. This investigation explores the issues of the Nigerian Police road traffic operatives along a heavy traffic highway in North Central Nigeria that qualify their unprofessional attitudes and behaviors, with possible insights to advance knowledge for policies towards improving service delivery. We collected data from police officers of two police formations in the research area, by quantitative survey. Also from the same two locations and another location, we collected qualitative data by applying in-depth analyses of opinion leaders. We applied Herzberg’s two factor theory and observed that lack of both motivators and hygiene factors seem to be impacting the operatives negatively hence they are not motivated to operate effectively. Data suggest that the Police immediate constraints are mainly hygiene factors (monetary rewards, welfare, tools, among others) which build up frustration and predispose them to oppression and extortion of road users, reflecting the overarching corrupt environment. The results support some earlier findings that both motivators and hygiene factors, not mainly motivators, drive employee motivation and performance. Policy implications include enhanced statutory spending and overhaul of the agency structure for improved employee performance.